2017
DOI: 10.1021/acsnano.7b00144
|View full text |Cite
|
Sign up to set email alerts
|

Strain Engineering for Anion Arrangement in Perovskite Oxynitrides

Abstract: Mixed-anion perovskites such as oxynitrides, oxyfluorides, and oxyhydrides have flexibility in their anion arrangements, which potentially enables functional material design based on coordination chemistry. However, difficulty in the control of the anion arrangement has prevented the realization of this concept. In this study, we demonstrate strain engineering of the anion arrangement in epitaxial thin films of the CaSrTaON perovskite oxynitrides. Under compressive epitaxial strain, the axial sites in TaON oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 28 publications
(54 reference statements)
2
40
0
Order By: Relevance
“…d High-pressure reactions. High pressure can prevent some reagents from dissociation or evaporation (upper) 22 – 26 , 41 , and also stabilize dense structures (lower) 27 . e Computational tools.…”
Section: Synthesis Beyond Heat and Beatmentioning
confidence: 99%
See 1 more Smart Citation
“…d High-pressure reactions. High pressure can prevent some reagents from dissociation or evaporation (upper) 22 – 26 , 41 , and also stabilize dense structures (lower) 27 . e Computational tools.…”
Section: Synthesis Beyond Heat and Beatmentioning
confidence: 99%
“…XANES is also effective for identifying the above elements and determining their chemical states. Perovskite (Ca 1– x Sr x )TaO 2 N epitaxial films with controlled strains were analyzed using XANES with a polarized light source 41 . From the intensity of π-bonded states of O or N with Ta-5 d via excitation from O and N core levels, it was concluded that N preferably takes the trans configuration in the TaO 4 N 2 octahedron for compressive strain states, which was also supported by STEM-EELS and DFT calculations (Fig.…”
Section: Chemical and Structural Analysesmentioning
confidence: 99%
“…7). To increase the epitaxial strain from substrate, Oka et al synthesized a series of Ca1-xSrxTaO2N films on SrTiO3 substrate and achieved the largest tetragonal strain of c/a ~ 1.05 at x = 0.5 [ 67 ]. Lineally polarized-X-ray absorption near edge structure (LP-XANES) measurements and scanning transmission microscope-electron energy loss spectroscopy of the Ca0.5Sr0.5TaO2N film directly proved that the axial anion sites were predominantly occupied by nitrogen as a result of trans-type N arrangement (Fig.…”
Section: Strain Engineering Of Anion Arrangement For Synthesis Of Metmentioning
confidence: 99%
“…As mentioned above, the TaO 4 N 2 octahedra in ATaO 2 N are exclusively of cis configuration, but the short-range-ordered state with zigzag -M-N-M-N-chains is not polar (or ferroelectric), which is unfortunate given the more polarizable nature of nitride anions compared with oxide anions. However, the recent thin film study of SrTaO 2 N and its Ca-substituted solid solution has shown that the application of compressive biaxial strain from a SrTiO 3 (STO) substrate induces a partial transformation to trans [12,13], leading to ferroelectric behavior [12].…”
Section: Low-temperature Reduction Of Srvo3 Filmsmentioning
confidence: 99%
“…The broad FWHM observed in the XRD profiles for the 12h-reacted film (Figure 2a) implies either a certain local variation in anion ordering or buckled [VO 2−x H x ] layers as observed in Ln-doped SrFeO 2+δ [21]. Further studies are necessary to clarify the anion arrangement of this intermediate phase, using, e.g., linearly polarized X-ray absorption spectroscopy as utilized to determine cis/trans-TaO 4 N 2 configuration in Ca-doped SrTaO 2 N [13].…”
Section: The Role Of Tensile Strainmentioning
confidence: 99%